Widespread Distribution of chs-1 Mutations Associated with Resistance to Diflubenzuron Larvicide in Culex pipiens Across Italy, Reaching Virtual Fixation in the Venetian Lagoon - Martina Micocci; Verena Pichler; Paola Serini; Carola Giammarioli; Chiara Malandruccolo; Chiara Virgillito; Marco Ballardini; Riccardo Paolo Lia; Daniele Arnoldi; Stefano Vettore; Davide Bonetto; Simone Martini; et al. (Insects, 2025)
Control interventions against mosquito larvae are the primary measure to reduce the adult abundance and risk of arbovirus outbreaks in Europe. One of the most commonly used larvicides in Italy is diflubenzuron (DFB), which targets chitin synthase 1 (chs-1), interrupting the normal development of larvae into adults. Recent studies identified high levels of DFB resistance in Culex pipiens populations from Emilia-Romagna (Italy) associated with I1043L/M/F mutations at position 1043 of the chs-1 gene. The aim of the present study was to assess the circulation of 1043 resistance alleles in Cx. pipiens populations across Italy, outside Emilia-Romagna, with a focus on the Veneto region. Overall, 1032 specimens were genotyped. The 1043L allele was found in all examined Italian regions (Trentino-Alto Adige 19–36%; Veneto 0–91%; Piemonte 11%; Liguria 28%; Lazio 0–8%; Puglia 5%). The highest frequencies (up to >90%) were observed in the Venetian lagoon, where 1043M was also detected (6–11%). Overall, the relatively low frequencies of 1043 mutations despite extensive and longstanding use of DFB in Italy suggest a high fitness cost worthy of further investigations, while their extremely high frequencies in coastal touristic sites point to these sites as the most relevant for resistance monitoring and larvicide rotation.